Effects of hemodialysis on upper airways collapsibility in patients with chronic kidney disease - Santos, Israel Reis; Danaga, Aline Roberta; Silva, Anderson Soares; Urbano, Jessica Julioti; Oliveira, Ezequiel Fernandes; Peixoto, Roger Andre de Oliveira; Guimarães, Letícia Lopes; Oliveira, Patrícia Clemente; Queiroz, Bruno Carlos de; Gonçalves, Caroline de Freitas; et al. (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: The Chronic Kidney Disease (CKD) is characterized as a clinical condition wherein the progressive loss of renal function for a period longer than months to years will lead to the onset of end-stage renal disease (ESRD). In the advanced stages of CKD, patients can only be treated with replacement therapy, dialysis or transplantation. In this context, hemodialysis (HD) presents as the main treatment option for these patients due to the lack of donors. Patients with ESRD in HD often present signs and symptoms related to pre-existing or acquired comorbidities with worsening of the disease. The most frequent are electrolytic disturbances, anemia, malnutrition, bone disease, Melittus diabetes, systemic arterial hypertension, gastrointestinal disorders, respiratory disorders, cardiovascular diseases, neurological changes and sleep disorders. Obstructive sleep apnea (OSA) presents a tenfold prevalence in patients with ESRD when compared to the general population, worsening the clinical symptoms and cardiovascular complications of this disease. The increase in the number of ESRD patients submitted to HD has assumed epidemic proportions worldwide. The causal association between sleep-disordered breathing, in particular OSA and ESRD, is still not well understood, which expands the possibility of new findings for the prevention, diagnosis and treatment of OSA, improving quality of life and reducing morbimortality. Objective: The present study involving ESRD patients undergone HD was designed with three main objectives: 1) to verify the prevalence and severity of sleep-disordered breathing; 2) to analyze the behavior of sleep apnea / hypopnea index (AHI) during the interdialitic period; 3) to verify weight gain and anthropometric measurements during the interdialitic period. Method: A consecutive single-center cross-sectional clinical study will be performed, double-blind, non-randomized to investigate the behavior of AHI in patients with ESRD undergoing HD in the nephrology unit (UNEFRO) at the Hospital of Santa Casa de Misericordia de Avaré, (SP), Brazil. The design and conduct of this study followed the guidelines of the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) statement